1996
DOI: 10.1073/pnas.93.13.6583
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the transcriptional coactivator and antirepression functions of transcription factor IIA.

Abstract: Human transcription factor IIA (TFIIA) is composed of three subunits (a, f3, and y). TFIIA interacts with the TATA-box binding protein and can overcome repression of transcription. TFIIA was found to be necessary for VP16-mediated transcriptional activation through a coactivator function. We have separated the coactivator and antirepression activities of TFIIA. A TFIIA lacking the a subunit was isolated from HeLa cells. This "mini-TFIIA" interacts with the TATA-box binding protein and can overcome repression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 55 publications
(99 reference statements)
5
31
0
Order By: Relevance
“…The loss of interaction is not due to global changes in the structure of the protein, since these Toa2 derivatives interact normally with the other subunit of TFIIA (both in vivo and in vitro), are expressed in cells at levels similar to that in wild-type Toa2, and are functional for TFIIA-TBP interactions in vitro. Although the 4HB of TFIIA is not involved in either TBP or DNA interactions in the crystal structures, a deletion derivative of human TFIIA lacking two of the helices in this domain is not responsive to activators in vitro (54). Taken together with our results, this suggests that the 4HB domain of TFIIA is a functionally important target that facilitates formation of an active transcription initiation complex.…”
Section: Fig 8 Transcriptional Analysis Of Activator-induced Genessupporting
confidence: 54%
“…The loss of interaction is not due to global changes in the structure of the protein, since these Toa2 derivatives interact normally with the other subunit of TFIIA (both in vivo and in vitro), are expressed in cells at levels similar to that in wild-type Toa2, and are functional for TFIIA-TBP interactions in vitro. Although the 4HB of TFIIA is not involved in either TBP or DNA interactions in the crystal structures, a deletion derivative of human TFIIA lacking two of the helices in this domain is not responsive to activators in vitro (54). Taken together with our results, this suggests that the 4HB domain of TFIIA is a functionally important target that facilitates formation of an active transcription initiation complex.…”
Section: Fig 8 Transcriptional Analysis Of Activator-induced Genessupporting
confidence: 54%
“…7), we found that RXR:VDR facilitated the assembly of TBP:TFIIA, TBP:TFIIA:TFIIB, and TBP:TFIIB by recruitment into higher-mobility complexes on a VDRE-linked promoter and that 1,25(OH) 2 D 3 enhanced the formation of these complexes, particularly in the presence of TFIIA. Enhanced activator responsiveness mediated through TFIIA, especially in more defined transcription assays involv- ing TFIID, has previously been demonstrated and may be involved in counteracting inhibitory components of TFIID (17,61,108). While we cannot rule out contributions of RXR:VDR to elongation of transcription, as has been described for other activators (107), our results suggest that direct stabilization of GTF complexes by RXR:VDR is one way in which the receptors mediate transcriptional enhancement.…”
Section: Discussionsupporting
confidence: 55%
“…Among these are general transcription factor IIA (Roeder, 1991;Cortes et al, 1992;Ma et al, 1996), transcription factor E2A (Murre et al, 1989;Melloul et al, 2002), Hu antigen D (Keene, 2001;Perrone-Bizzozero and Bolognani, 2002;Park-Lee et al, 2003), and Sox 17 (Kanai et al, 1996;Kanai-Azuma et al, 2002). It is interesting that these widely expressed, transcriptionally related gene products are preferentially expressed in the SON relative to the hypothalamus, with expression ratios ranging from 3.8 to 5.1 (Table 2), again likely correlating with the high rates of transcription that occur in the SON (Burbach et al, 2001).…”
Section: Discussionmentioning
confidence: 99%